4(x-7)-2=2(x-3)

Simple and best practice solution for 4(x-7)-2=2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-7)-2=2(x-3) equation:


Simplifying
4(x + -7) + -2 = 2(x + -3)

Reorder the terms:
4(-7 + x) + -2 = 2(x + -3)
(-7 * 4 + x * 4) + -2 = 2(x + -3)
(-28 + 4x) + -2 = 2(x + -3)

Reorder the terms:
-28 + -2 + 4x = 2(x + -3)

Combine like terms: -28 + -2 = -30
-30 + 4x = 2(x + -3)

Reorder the terms:
-30 + 4x = 2(-3 + x)
-30 + 4x = (-3 * 2 + x * 2)
-30 + 4x = (-6 + 2x)

Solving
-30 + 4x = -6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-30 + 4x + -2x = -6 + 2x + -2x

Combine like terms: 4x + -2x = 2x
-30 + 2x = -6 + 2x + -2x

Combine like terms: 2x + -2x = 0
-30 + 2x = -6 + 0
-30 + 2x = -6

Add '30' to each side of the equation.
-30 + 30 + 2x = -6 + 30

Combine like terms: -30 + 30 = 0
0 + 2x = -6 + 30
2x = -6 + 30

Combine like terms: -6 + 30 = 24
2x = 24

Divide each side by '2'.
x = 12

Simplifying
x = 12

See similar equations:

| 5k-2k=-21 | | 368317*10= | | 10x-8=9x-5 | | 458000*8= | | -16=-3p+p | | 449000*8= | | 3n=4n-4 | | 8n+3n=-22 | | 2x+26=44 | | 2x+10=x+36 | | 35-14=-35 | | 96+x=40x | | 5x+100=-235 | | -6s=36 | | y=(1-x)/1.2 | | (x+7)(x-2)=(x+1)(x+1) | | 1.4(x+1.2)=7.8 | | -24/5=31/2h | | (x+7)(x+2)=(x+1)(x+1) | | m=z+bx | | 12x+8y+7x=z | | 2(3x-4)+6(x-5)=-3(4-5x)+5x-16 | | 4y-1x+2y=z | | [8+(-4)]-5= | | -8/12-21/12 | | 12+[-5+(-4)]= | | (7/x)-(1/7)=(2/x) | | 3(3x-2)=15 | | 2(3x-5)+6(x-3)=-3(3-5x)+5x-1 | | 2-4(x+3)=4-2(3x+5) | | 2.5=2/s | | -2(-3)-5y=4 |

Equations solver categories